Mapping Macroeconomic Risks of Global Climate Policies: A Systematic Literature Review - Rahmi Afzhi Wefielananda; Hesty Aisyah (Journal of Enterprise and Development (JED), 2026)
Purpose: This study aims to map the macroeconomic risks arising from global climate policies in the international economics literature, identify transmission mechanisms, examine the role of climate policy uncertainty, and explore the thematic evolution of existing studies.Method: The study employs a Systematic Literature Review based on the PRISMA protocol, applied to Scopus-indexed articles using keywords related to macroeconomic climate risks and climate policy spillovers. From 82 initial documents, 33 core studies were selected and analyzed thematically and comparatively.Result: This research found that the macroeconomic risks of climate policies are transmitted through four main channels: energy and carbon markets, financial markets, international trade and exchange rates, and institutional and behavioral dimensions. Climate policy uncertainty increases volatility and extreme risks during market stress and triggers cross-sectoral and cross-country spillovers. The literature reveals that financial markets act as the primary mediator between climate policies and macroeconomic stability, while the exchange rate channel operates through changes in global energy prices. The thematic evolution shows a shift from environmental issues toward macroeconomic and financial stability, with a growing dominance of quantile and time-frequency approaches.Practical Implications for Economic Growth and Development: The study concludes that global climate policies constitute a key determinant of international macroeconomic stability and require an integrated analytical approach across markets and sectors to support sustainable growth and development.Originality/Value: This study reformulates global climate policy as a systemic macroeconomic risk architecture that integrates the energy, financial, trade, and institutional channels, which have previously been examined in a fragmented manner.